2010
DOI: 10.1111/j.1462-2920.2010.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation

Abstract: A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (< 50%) with known sequences. By phylogenetic analysis, these sequences were separated into three clusters that showed substantial diversity. The two most abundant cysteine phytas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
3
29
0
1
Order By: Relevance
“…The GFP gene harbored in recombinant P. pastoris was confirmed to have no cross-reaction with the DNA or cDNA of the rumen sample and was therefore suitable for use for normalizing for technical variations between rumen samples. Copy numbers for each gene matched the gene's abundance (based on sequencing data), thus confirming that there was no primer-associated bias; this is in agreement with the report by Huang et al (25). Quantitative analysis at the transcriptional level of the six representative xylanase genes at four time points showed that all six genes had lowered transcription at 4 h, and then four of the genes (including those having the highest and lowest abundance) were gradually upregulated.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The GFP gene harbored in recombinant P. pastoris was confirmed to have no cross-reaction with the DNA or cDNA of the rumen sample and was therefore suitable for use for normalizing for technical variations between rumen samples. Copy numbers for each gene matched the gene's abundance (based on sequencing data), thus confirming that there was no primer-associated bias; this is in agreement with the report by Huang et al (25). Quantitative analysis at the transcriptional level of the six representative xylanase genes at four time points showed that all six genes had lowered transcription at 4 h, and then four of the genes (including those having the highest and lowest abundance) were gradually upregulated.…”
Section: Discussionsupporting
confidence: 82%
“…We retrieved 44 distinct GH 10 xylanase gene fragments (Ͻ95% identity) from the rumen using a culture-independent approach. These fragments had shared identities with known xylanases in GenBank as low as 39%, which further confirms that there are large numbers of unidentified genes in the rumen ecosystem (25,26). Most of the retrieved GH 10 xylanase gene sequences showed significant expression variation at the genomic and transcriptional levels.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Rumen metagenome libraries have also been used to screen for other bioactivities, including novel lipases (Liu et al, 2009a;Bayer et al, 2010), polyphenol oxidase (Beloqui et al, 2006) and an enzyme capable of degrading 3,5,6-trichloro-2-pyridinol, a degradation product of the organophosphorus insecticide chlorpyrifos (Math et al, 2010). In addition, cysteine phytases have been isolated by screening ruminal genomic DNA from cows and goats using degenerate primer sets (Huang et al, 2010). Functional metagenomics has the potential to uncover new enzymes and metabolic pathways in the rumen if innovative strategies for screening are developed.…”
Section: The Quest For Functions Through Metagenomicsmentioning
confidence: 99%